Tinjauan Literatur: Pengaruh Pajak Daerah terhadap Pendapatan Asli Daerah - Ulhaq, Ghinaa Rizki Dhiya; Widajantie, Tituk Diah (Jurnal KIAFE, 2026)
This study aims to analyze the effect of local taxes on Local Own-Source Revenue through a literature review approach. The main issue addressed in this study is the suboptimal contribution of local taxes to Local Own-Source Revenue in several regions in Indonesia, as reflected in previous studies with varying findings. This research uses a descriptive qualitative method by reviewing six relevant national journal articles published within the 2021–2025 period. The findings show that local tax effectiveness generally has a positive effect on Local Own-Source Revenue in several regions. However, the contribution of local taxes to Local Own-Source Revenue varies across regions. Some regions show a positive contribution, while others still record relatively low contribution levels. Several studies also indicate that local tax effectiveness declined during the COVID-19 pandemic but improved again in subsequent years. These findings highlight the importance of strengthening local government tax management capacity, improving tax collection strategies, and optimizing regional tax potential to increase fiscal independence and support public welfare.